Bangladesh Ship Breaking Industry and Livelihood Assessment of Out-Migrant Workers: A Study of Southern - Northern Region in Bangladesh - Chowdhury, Ahmed Imtiaz; Islam, Saiful; Era, Samiha Tasnim (International Journal of Social Science and Religion (IJSSR), 2024)
Since 1971, the shipbreaking industry in Bangladesh has grown rapidly, employing approximately 40,000 to 50,000 underprivileged workers from the most underdeveloped regions of Bangladesh. After working for 15-20 years, they leave this industry for different sorts of physical problems, which lead to a low quality of life. Therefore, this paper aims to explore the livelihood status of the out-migrant workers in the shipbreaking industry of Bangladesh. The instruments used for this research were a semi-closed-ended survey questionnaire, in-depth interviews, ethnographic participant observation, and secondary research. The respondents are from the southern and northern parts of Bangladesh, aged 18 years and older. This study has discovered no significant differences between northern and southern out-migrant workers in asset ownership, goods, or housing quality. However, the southern out-migrant population earned relatively more than the northern migrants due to better access to capital and institutional support. This study also shows that after working a few years, young people desire to do external migration for better income opportunities. Despite minimal overall improvement in livelihood status, southern migrants earn comparatively better. Therefore, the government and other stakeholders must bridge the gap of unequal socio-economic development between the southern and northern regions.